2011
DOI: 10.1103/physreva.84.062324
|View full text |Cite
|
Sign up to set email alerts
|

M-ary-state phase-shift-keying discrimination below the homodyne limit

Abstract: We investigate a strategy for M-ary discrimination of nonorthogonal phase states with error rates below the homodyne limit. This strategy uses feed forward to update a reference field and signal nulling for the state discrimination. We experimentally analyze the receiver performance using postprocessing and a Bayesian strategy to emulate the feed-forward process. This analysis shows that for a moderate system detection efficiency, it is possible to surpass the homodyne error limit for quadrature phase-shift ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
84
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(91 citation statements)
references
References 12 publications
5
84
1
1
Order By: Relevance
“…However, it is one of the innermost consequences of the laws of quantum mechanics that nonorthogonal states cannot be discriminated with certainty. Optimal detection strategies were first investigated by Helstrom [20,21] and Holevo [22] and a lot of attention has since been devoted to the development of optimal and near-optimal receivers for binary coherent states [23][24][25][26][27][28][29][30][31][32] and for the discrimination of larger signal alphabets [33][34][35][36][37][38][39][40][41]. An overview over different receiver schemes is provided in Appendix B.…”
Section: Binary Coherent-state Cloningmentioning
confidence: 99%
“…However, it is one of the innermost consequences of the laws of quantum mechanics that nonorthogonal states cannot be discriminated with certainty. Optimal detection strategies were first investigated by Helstrom [20,21] and Holevo [22] and a lot of attention has since been devoted to the development of optimal and near-optimal receivers for binary coherent states [23][24][25][26][27][28][29][30][31][32] and for the discrimination of larger signal alphabets [33][34][35][36][37][38][39][40][41]. An overview over different receiver schemes is provided in Appendix B.…”
Section: Binary Coherent-state Cloningmentioning
confidence: 99%
“…1, in the Becerra et al experiment of ref. [39] (Our slices are referred to therein as "stages"). In their more recent experiment in ref.…”
Section: Sequential Waveform Nulling Receivermentioning
confidence: 99%
“…Bondurant proposed a receiver for the 4-ary Phase Shift Keying (QPSK) constellation that is exponentially optimal [38]. Recently, Becerra and collaborators proposed a feedforward receiver structure for M -ary PSK with arbitrary M and demonstrated that it closely approximates the Helstrom limit for 4-PSK, in a partially simulated experiment without real-time switching of the local oscillator (LO) field [39]. In work that is to appear [40], the Becerra group has implemented their receiver for 4-PSK with real-time switching of the LO and demonstrated that it beats the standard quantum limit, i.e., the performance of the ideal heterodyne receiver, even without adjusting for detection inefficiency and other realistic limitations for average input photon numbers in the range of N = 2 − 15.…”
mentioning
confidence: 99%
See 2 more Smart Citations